COMPARISON OF ANTIMICROBIAL ACTIVITY OF TWO POLYMERIC GUANIDINE DERIVATIVES - Lysytsya, Andriy; Kryvoshyya Pavlо (Collection of scientific papers «ΛΌГOΣ», 2023)
The polymeric guanidine derivatives have long proven to be efficient disinfectants and antiseptics. They have clearly expressed bactericidal, virucidal, fungicidal, and algicidal properties [1, 2]. There is much information on the application of polymeric guanidine derivatives in the composition of different disinfectants and antiseptics, for instance, e.g., in the treatment of hospital-acquired infections (biofilms) [2, 3, 4]. In addition, polyhexamethylene guanidine (PHMG), has also been used with some effect in the purification of sewage and underground waters [5].